Model faktor kejayaan kritikal projek pembangunan semula perumahan rakyat akibat gempa bumi di Indonesia - Farni, Indra (2022)
The rebuilding of community homes after earthquakes is a process that provides basic needs and promote economic recovery as nell as income sources for the affected community. In Indonesia, the effectiveness of the implementation of post-earthquake community home reconstruction projects still needs to be improved due to the presence of various problems such as poor coordination among rehabilitation and reconstruction agencies, ineffective construction management strategies, low contractor capacity, and lack of community involvement. All these problems need to be looked at in depth and addressed more effectively. The aim of this study is to develop a model that can help to improve the management of post-earthquake community home reconstruction projects by identifying the factors that guarantee the success of project implementation as well as their relationship with project performance. The identified success factors are relevant to the characteristics of reconstruction projects in Indonesia. This study employs a combination of qualitative and quantitative methods. The main methodology in this study involved semi-structured interviews with post-earthquake reconstruction experts, questionnaire survey to stakeholders, data analysis by using the Statistical Package for Social Sciences (SPSS) software and the formation of a structural model of the relationship between critical factors and project performance based on the Partial Least Square – Structural Equation Modeling (PLS-SEM) method. Data analysis shows that in the context of community home redevelopment projects in Indonesia, a total of eleven problems that frequently occur have been identified in line with the problems discovered through the literature review. These problems relate to damage assessment, community involvement, land grants, openness and accountability, funding adequacy, strategy and policy, resource availability, communication and coordination, staff experience and ability, technical specifications and disaster risk reduction, where each one has a positive relationship and contributes significantly to the problems in post-earthquake community home redevelopment projects. This study also successfully identified 34 important factors that influence the success of post-earthquake redevelopment projects which can be grouped into four distinct stages of project development, namely the Initiation Stage, Planning Stage, Implementation Stage, and Closing Stage. The four stages of project development are constructs resulting from Factor Analysis. This finding allows a PLS-SEM model to be developed that explains the relationship between Critical Success Factors and Project Performance for post-earthquake community home reconstruction projects in Indonesia. Hypothesis testing confirmed that the Planning Stage and Project Closing Stage have significant relationships with Project Performance. In addition, a guideline has been successfully developed from the resulting model, making it a practical document that can be used by various parties involved in post-earthquake community home reconstruction projects in Indonesia. It will be the main reference for stakeholders in Indonesia to plan and implement future reconstruction projects.